A Review on the Remedies Arranged in the Misdemeanors Law Against Decisions of Administrative Sanction - Muhammet Kahveci (İstanbul Hukuk Mecmuası)
With the enactment of the Misdemeanour Code No. 5326, which aims to establish a system for misdemeanours that are dispersed throughout the legislation, various controversial issues have emerged. Applications have been lodged with the Constitutional Court claiming that some articles of the Code are unconstitutional. Accepting the judicial judiciary as a general jurisdictional judicial remedy in the provisions concerning remedies has led to discussions on the constitutional division of jurisdiction between the judicial and administrative judiciary. Differences in opinion have also arisen regarding the provisions of the Misdemeanours Code concerning remedies. In particular, it has been debated whether a decision on an administrative sanction, which is subject to legal remedies under the Misdemeanours Code, can also be subject to extraordinary legal remedies under the Criminal Procedure Code. Different opinions have been expressed in the literature on the subject. These debates and uncertainties have also been reflected in practise and court decisions. The case law of the Constitutional Court and the Court of Cassation has changed over time.